Radiation-induced ovarian follicle loss occurs without overt stromal changes. Issue 6 (June 2018) - Kimler, Bruce F; Briley, Shawn M; Johnson, Brian W; Armstrong, Austin G; Jasti, Susmita; Duncan, Francesca E
Abstract : Radiation damage due to total body irradiation (TBI) or targeted abdominal radiation can deplete ovarian follicles and accelerate reproductive aging. We characterized a mouse model of low-dose TBI to investigate how radiation affects the follicular and stromal compartments of the ovary. A single TBI dose of either 0.1 Gy or 1 Gy (Cesium-137 γ) was delivered to reproductively adult CD1 female mice, and sham-treated mice served as controls. Mice were euthanized either 2 weeks or 5 weeks post exposure, and ovarian tissue was harvested. To assess the ovarian reserve, we classified and counted the number of morphologically normal follicles in ovarian histologic sections for all experimental cohorts using an objective method based on immunohistochemistry for an oocyte-specific protein (MSY2). 0.1 Gy did not affect that total number of ovarian follicles, whereas 1 Gy resulted in a dramatic loss. At two weeks, there was a significant reduction in all preantral follicles, but early antral and antral follicles were still present. By five weeks, there was complete depletion of all follicle classes. We examined stromal quality using histologic stains to visualize ovarian architecture and fibrosis and by immunohistochemistry and quantitative microscopy to assess cell proliferation, cell death and vasculature. There were no differences in the ovarian stroma across cohorts with respect to these markers, indicating that this compartment is more radio-resistant relative to the germ cells. These findings have implications for reproductive health and the field of fertility preservation because the radiation doses we examined mimic scatter doses experienced in typical therapeutic regimens.